Legal Certainty and Legal Protection in the Implementation of Disciplinary Punishments for State Civil Apparatus in Light of Statutory Norms - Teguh Setiyawan; Muchlas Rowi (Indonesian Journal Publisher, 2026)
The State Civil Apparatus (ASN) operates based on behavioral standards derived from statutory law and moral principles. Statutory law is reflected in formal regulations, while moral guidance is embodied in the ASN code of ethics. Issues arise when an ASN’s conduct is considered compliant from a legal standpoint (i.e., not in violation of applicable norms), but is deemed problematic from a moral perspective and therefore subject to disciplinary measures. This dual framework creates uncertainty, making disciplinary actions difficult to assess objectively and prone to arbitrary implementation. In some cases, such actions may even be misused in ways that contradict their intended purpose, namely to uphold the dignity of the State Civil Apparatus. This study employs an empirical juridical method, with data collected from the Agency for Policy Strategy and Legal and Judicial Education and Training, as well as from several courts within the administrative jurisdiction of Bogor City. The purpose of this study is to determine the practice of enforcing the code of ethics and identify the legal norms that regulate the ASN code of ethics behavior, while also understanding how the enforcement mechanism is in accordance with the good and correct rule of law. This research finds that the norms governing disciplinary sanctions for civil servants in positive law create confusion in the development of civil servants. Several positive legal norms conflict with one another, thereby threatening three fundamental elements of the rule of law: the supremacy of law, equality before the law, and the protection of human rights.